Ameliorative effect of selegiline in high fat diet induced obesity rat model: Possible role of dopaminergic pathway. (December 2020) - Goyal, Amit; Sharma, Ankita; Sharma, Deepika; Behl, Tapan; Kamboj, Anjoo; Babu, Arockia
Abstract: Objectives: Dopamine a neurotransmitter plays an important role in food regulation. Various reports revealed that suppression of dopamine results in pathological overeating. Monoamine oxidase type B (MAO-B) inhibitor selegiline (SG) increases the level of dopamine in the brain. Thus, the current study was designed to examine whether selegiline (SG) could attenuate the development of experimental obesity and to explore the possible involvement of dopamine in high fat diet (HFD) induced obesity. Materials and methods: Current study illustrates importance of administrating SG (10 and 20 mg kg −1 day −1, p. o.) alone and SG (20 mg kg −1 day −1, p. o) in combination with chlorpromazine (CPZ) (6 mg kg −1 day −1 p.o) in obesity. The SG and its combination with CPZ were given orally for 6 weeks along with high fat diet to the obese rats. The body weight, feed intake (Kcal), weight and size of fat pads, levels of serum glucose, triglycerides (TG), total cholesterol (TC), low density lipoprotein (LDL), very low-density lipoprotein VLDL and high density lipoproteins (HDL) were estimated as parameters of obesity. Results: Oral administration of SG (10 and 20 mg kg −1 day −1 ) significantly reduced (p < 0.05) body weight gain, feed intake (Kcal), weight and size of fat pads, levels of serum glucose, TG, TC, LDL, VLDL in obese rats. Furthermore, Dopaminergic antagonist CPZ in combination with SG declines the beneficial effects of SG in obese rats. Conclusion: The present study demonstrates the involvement of dopaminergic pathway and beneficial effects of dopamine enhancer SG in HFD induced obesity. Highlights: There is a relationship between HFD intake and neurotransmitter concentration in the rat brain. Dopaminergic pathway play important role in obesity. Selegiline a dopamine enhancer have beneficial effects in obesity. Chlorpromazine in combination with selegiline declines the beneficial effects of selegiline in obese rats.